29th International Conference on Ocean, Offshore and Arctic Engineering: Volume 6 2010
DOI: 10.1115/omae2010-20373
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Manoeuvring Forces on Submarines Using Two Viscous-Flow Solvers

Abstract: Submersibles used for exploration, maintenance and naval warfare have to be both manoeuvrable and easy to control. Simulation of the trajectory for these vessels requires the accurate determination of the hydrodynamic forces and moments which are determined by model-testing, empirical methods or a combination of both. CFD can play a role here by permitting an easier and more accurate determination of these loads. In this paper we focus on the accurate prediction of the manoeuvring forces of free swimming strea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Our application of CFD was relatively superficial compared to other studies that have used CFD to numerically model the flow around AUVs and particularly for investigating its wake (Falcao de Campos, 1983;Tyagi and Sen, 2006;Phillips et al, 2007;de Barros et al, 2008;Wu, 2010;Vaz et al, 2010). The authors thank an anonymous reviewer for providing these references.…”
Section: Numerical Modellingmentioning
confidence: 95%
“…Our application of CFD was relatively superficial compared to other studies that have used CFD to numerically model the flow around AUVs and particularly for investigating its wake (Falcao de Campos, 1983;Tyagi and Sen, 2006;Phillips et al, 2007;de Barros et al, 2008;Wu, 2010;Vaz et al, 2010). The authors thank an anonymous reviewer for providing these references.…”
Section: Numerical Modellingmentioning
confidence: 95%
“…These values are then compared with respect to the theory; see the works by the authors of [14,15]. Validation of the model can also be carried out with respect to simulations using Computational Fluid Dynamic (CFD) simulation software [16,17], which requires a correct simulation configuration [18]. Another way to use the PMM for identification is by turning on the robot’s actuators and finding the relationship between the energy input and the force and torque in the output generated by the robot [19].…”
Section: Introductionmentioning
confidence: 99%
“…For larger Reynolds number environment (laminar flow), the seawater would be removed from the submarine' surface and form complex vortex street, which will cause large fluid dynamics fluctuation. Previous researchers [3] [4] have done a lot of researches on underwater vehicles. They found that the yawing, pitching and rolling three disturbance trends of movement would be caused by the moments vehicles suffering, which could inevitably increase the angle tracking error of the submarine tracking-pointing device.…”
Section: Introductionmentioning
confidence: 99%